A SEMIOTIC ANALYSIS FOUND ON KOPI KAPAL API SPECIAL MIX RAMADHAN EDITION ADVERTISEMENT - Mukhlasul Fasikh; Abdul Muhid Murtadho (Journal of English Language and Literature (JELL), 2020)
In this study, the writer did a semiotic analysis towards the advertisement in television. The qualitative research method with content analysis approach is used because this study needs deeper analysis of the content where in this study was semiotic signs. It is found that the man in the picture is very special. He delivers happiness and togetherness condition. The happiness and togetherness are most displayed in this advertisement. Happiness is shown when People are able to start to chat without any gap easily and happily. Togetherness is displayed when people gather together in the café. The other sign is the strong aroma of the coffee that reminds the man about his past